2015
DOI: 10.1016/j.fertnstert.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Noninferiority, randomized, controlled trial comparing embryo development using media developed for sequential or undisturbed culture in a time-lapse setup

Abstract: NCT01939626.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…In lower resource settings or in any setting addressing cost, a single medium could infer distinct economic advantages. Moreover, compatibility with time-lapse systems is undoubtedly a significant benefit and a key reason for the increasing popularity of continuous single medium protocols [20,35,40,60]. Of note, however, current evidence does not suggest a clear benefit of using time-lapse for embryo selection, and these systems generally increase the overall cost of the IVF procedure [62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In lower resource settings or in any setting addressing cost, a single medium could infer distinct economic advantages. Moreover, compatibility with time-lapse systems is undoubtedly a significant benefit and a key reason for the increasing popularity of continuous single medium protocols [20,35,40,60]. Of note, however, current evidence does not suggest a clear benefit of using time-lapse for embryo selection, and these systems generally increase the overall cost of the IVF procedure [62].…”
Section: Discussionmentioning
confidence: 99%
“…We further examined 23 studies for eligibility: -A total of three studies were excluded: Two studies used Fertilization and then Cleavage Medium and not a system for Cleavage and then Blastocyst [20,21], and one study was excluded because a different oxygen tension was used in the different groups [22]. -A total of 20 studies were included in this review: Ten studies that randomized oocytes/zygotes [23][24][25][26][27][28][29][30][31][32] and two studies that randomized women [33,34] were included in the forest plots; however, six studies that randomized oocytes/zygotes [35][36][37][38][39][40] and two studies that randomized women [41,42] were not included in the forest plots because it was not possible to extract data for the metaanalyses.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, KSOM AA medium entered the Life Global marketplace as Global ® medium (LG; [48]), which was optimized as a single use medium that worked under the principle that embryos will select what they need at changing developmental stages. These diverging concepts continue today, although the increase acceptance of single-step media, especially in conjunction with time lapse imaging [49,50], has spurred more companies to develop additional single use media. Both Gardner and Lane [19,21,25], as well as Biggers and associates [34,48,51] provided us with sound science supporting their formulations and aimed to minimize embryo stress through consistency in amino acid and antioxidant supplementation, as well as using stable dipeptides of l-glutamine that minimized ammonium waste-product production [26,34,35,52].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven morphokinetic parameters were evaluated, and only four parameters (t7, t8, t3c4c-time between the irst observation of 3 and 4 completely separated blastomeres, and t5c7c-time between the irst observation of 5 and 7 completely separated blastomeres) difer signiicantly between embryos cultured in altered media. The authors concluded that single-step culture medium is as nutrient as sequential media for blastocyst development [35]. Costa-Borges et al compared embryo morphokinetics in single culture media with and without medium renewal on Day 3 of culture.…”
Section: Efect Of the Type Of Culture Media On Embryo Morphokineticsmentioning
confidence: 99%